Beispiel Nr: 07
$\text{Gegeben:} \\ \text{Ebene1: } \vec{x} =\left( \begin{array}{c} a1 \\ a2 \\ a3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} b1 \\ b2 \\ b3 \\ \end{array} \right) + \sigma \left( \begin{array}{c} c1 \\ c2 \\ c3 \\ \end{array} \right) \\ \text{Ebene2: } n1 x_1+n2 x_2+n3 x_3+k1=0 \\ \\ \text{Gesucht:} \\\text{Lage der Ebenen zueinander} \\ \\ \textbf{Gegeben:} \\ \text{Ebene1: } \vec{x} =\left( \begin{array}{c} 1 \\ 4 \\ 3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 0 \\ 4 \\ 1 \\ \end{array} \right) + \sigma \left( \begin{array}{c} -2 \\ 0 \\ -\frac{1}{2} \\ \end{array} \right) \\ \text{Ebene2: } 1 x_1+1 x_2-4 x_3+4=0 \\ \\ \\ \textbf{Rechnung:} \\ \text{Ebene: } \vec{x} =\left( \begin{array}{c} 1 \\ 4 \\ 3 \\ \end{array} \right) + \lambda \left( \begin{array}{c} 0 \\ 4 \\ 1 \\ \end{array} \right) + \sigma \left( \begin{array}{c} -2 \\ 0 \\ -\frac{1}{2} \\ \end{array} \right) \\ \text{Ebene: } 1 x_1+1 x_2-4 x_3+4=0 \\ \begin{array}{cccc} x_1=& 1 &+0\lambda &-2\sigma \\ x_2=&4 &+4\lambda &+0\sigma \\ x_3=&3 &+1\lambda &+0\sigma\\ \end{array} \\ 1( 1+0\lambda-2\sigma) +1(4+4\lambda+0\sigma) -4 (3+1\lambda-\frac{1}{2}\sigma)+4=0 \\ 0\lambda+0\sigma-3=0 \\ \\ -3=0 \\\\ \text{Ebenen sind parallel} $